2022
DOI: 10.3389/fneur.2022.843801
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunology of CNS HIV Infection: A Narrative Review

Abstract: This short review provides an overview of the interactions of human immunodeficiency virus type 1 (HIV), immune and inflammatory reactions, and CNS injury over the course of infection. Systemic infection is the overall driver of disease and serves as the “platform” for eventual CNS injury, setting the level of immune dysfunction and providing both the HIV seeding and immune-inflammatory responses to the CNS. These systemic processes determine the timing of and vulnerability to HIV-related neuronal injury which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 103 publications
0
4
2
3
Order By: Relevance
“…This HIVassociated GM atrophy can potentially be attributed to the neurodegeneration from neurotoxic substances associated with HIV. 25 Although we did not find a baseline difference in GM, previous cross-sectional and longitudinal studies have similarly found GM reduction, even in in virally suppressed PLWH, compared with controls. 26,27 Others have reported no accelerated changes in GM volume in virologically controlled PLWH 9,28 ; however, these studies had strict exclusion criteria, such as exclusion of participants with extensive WMH, that may lead to a bias toward healthier individuals in the wider PLWH population.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This HIVassociated GM atrophy can potentially be attributed to the neurodegeneration from neurotoxic substances associated with HIV. 25 Although we did not find a baseline difference in GM, previous cross-sectional and longitudinal studies have similarly found GM reduction, even in in virally suppressed PLWH, compared with controls. 26,27 Others have reported no accelerated changes in GM volume in virologically controlled PLWH 9,28 ; however, these studies had strict exclusion criteria, such as exclusion of participants with extensive WMH, that may lead to a bias toward healthier individuals in the wider PLWH population.…”
Section: Discussioncontrasting
confidence: 76%
“…This is a reasonable finding given GM's pivotal role in information processing and motor control. This HIV‐associated GM atrophy can potentially be attributed to the neurodegeneration from neurotoxic substances associated with HIV 25 . Although we did not find a baseline difference in GM, previous cross‐sectional and longitudinal studies have similarly found GM reduction, even in in virally suppressed PLWH, compared with controls 26,27 .…”
Section: Discussioncontrasting
confidence: 68%
“…CNS/NP disturbances in PLWH are complex and the exact neuropathogenetic mechanisms are often challenging to highlight: usually, several intertwined factors coexist. For example, low CD4+ T cells count, unknown HIV status and poor drug compliance have great impact on the development of CNS/NP disturbances in PLWH and are significantly associated with development of CNS opportunistic infections, cerebrospinal fluid (CSF) viral escape, chronic cerebrovascular disease and HAND [13]. Furthermore, even in experienced patients under optimal antiretroviral therapy and acceptable viro-immunological conditions, it is unclear whether the CNS serves as a source and niche of perpetual neuroinflammation that contributes to the development of CNS/NP disturbances [14].…”
Section: N Introductionmentioning
confidence: 99%
“…A interação entre as células "invasoras" infectadas e as células residentes estabelece um ambiente inflamatório independente que evolui com o curso da doença 21 . Dessa forma, a replicação local do HIV nessas células, gera uma infecção geneticamente independente do que ocorre fora do SNC, dando início a um processo de compartimentalização que estabelece um segundo reservatório viral 22 O estágio da infecção do HIV influencia diretamente em seu efeito no SNC, sendo medido pela contagem de CD4 no sangue.…”
Section: Hiv E O Sistema Nervoso Centralunclassified
“…A partir disso, este projeto propõe o estudo do perfil de peptídeos encontrados no líquor de indivíduos com HIV, visando a possibilidade de serem utilizados como biomarcadores de progressão da HAND, como também para estudos de incidência. Além disso, a comparação dos resultados obtidos com os dados clínicos dos pacientes, oferece uma oportunidade única, possibilitando o desenvolvimento de novas abordagens para a prevenção e tratamento da HAND 21 .…”
Section: Alterações Cognitivas Associadas Ao Hivunclassified